Association of Vitamin D with severity and outcome of COVID-19: Clinical and Experimental Evidence - Georgios Renieris; Spyros Foutadakis; Theano Andriopoulou; Victoria-Marina Spanou; Dionysia-Eirini Droggiti; Dionysios Kafousopoulos; Theologia Gkavogianni; Georgia Damoraki; Giannis Vatsellas; Evangelos J. Giamarellos-Bourboulis (Journal of Innate Immunity, 2023)
Introduction: The role of vitamin in COVID-19 remains controversial. We investigated the association between endogenous vitamin D and the severity of COVID-19 as well as the mechanisms of action of vitamin D supplementation. Methods: 25(OH)D3 in serum was associated with disease severity and outcome in 190 COVID-19 patients. In a COVID-19 animal model using intravenous injection of plasma from patients with COVID-19 ARDS into C57/BL6 mice, mice were treated with 0.25μg human 1,25(OH)D3 or vehicle. Mice were sacrificed on day 4. Cytokines and myeloperoxidase (MPO) in tissues were measured. Changes in gene expression after vitamin D supplementation were measured. Results: Vitamin D deficiency and insufficiency were associated with increased severity and unfavourable outcome after 28 days. Vitamin D levels were negatively associated with biomarkers of COVID-19 severity. Vitamin D supplementation after challenge of mice with COVID-19 plasma led to reduced levels of TNFα, IL-6, IFNγand MPO in the lung, as well as down-regulation of pro-inflammatory pathways. Conclusion: Normal levels of endogenous Vitamin D are associated with reduced severity and risk of unfavourable outcome in COVID-19, possibly through attenuation of tissue-specific hyperinflammation.